Perception of bimodal warning cues during remote supervision of autonomous agricultural machines - Anita Chidera Ezeagba; Cheryl Mary Glazebrook; Daniel Delmar Mann (Research in Agricultural Engineering)
Agricultural machines that are fully autonomous will still need human supervisors to monitor and troubleshoot system failures. Recognising the emergency as soon as possible is crucial to reduce adverse effects. The ability of humans to detect visual, auditory, or tactile cues is usually enabled by warning systems. The effectiveness of different warning cues varies in terms of prompting a quick response. The study's objective was to compare the effectiveness of two bimodal warnings (i.e., visual-auditory and visual-tactile) at eliciting supervisor perception (which equates to level one situation awareness). Twenty-five participants engaged in an autonomous sprayer simulation. Two realistic remote supervision scenarios (i.e., in-field and close-to-field) were used to examine two bimodal warning cues: (i) visual-auditory and (ii) visual-tactile. The effectiveness of each bimodal warning was assessed based on two measures: (i) response time and (ii) noticeability. There was no significant difference between the bimodal warning cues in terms of response time when tractor sound was present in the experimental environment (reflecting the in-field remote supervision scenario); however, visual-tactile cues yielded shorter response times than visual-auditory cues when the experimental environment was quiet (reflecting the close-to-field remote supervision scenario). There were no statistically significant differences between visual-auditory and visual-tactile warnings concerning noticeability. Participants' subjective answers indicated they preferred the visual-tactile cues better than the visual-auditory cues. It is concluded that visual-tactile warnings are preferred over visual-auditory warnings to enable perception during remote supervision of autonomous agricultural machines (AAMs).